Cooperation of the Ministry of Internal Affairs of Ukraine with the Police Departments of the Countries of EU and NATO in the Field of Professional Training of Managerial Staff - I. Kuzmenko (Юридичний часопис Національної академії внутрішніх справ, 2021)
The purpose of the article is to study the essence and topical issues of cooperation between the Ministry of Internal Affairs of Ukraine and the police departments of the European Union and NATO in the field of management training. Methodology. The work uses general and special-scientific methods of cognition, the specific combination of which is determined by the purpose and objectives of the study. The use of the formal-logical method made it possible to define, clarify and supplement certain concepts, categories, to organize the conceptual-categorical apparatus. Methods of formal logic, in particular analysis and synthesis, deduction and induction, analogy and generalization, etc., are also used. The scientific novelty of the article is that it studies the cooperation of the Ministry of Internal Affairs of Ukraine with the police departments of the European Union and NATO at the current stage of state and legal development, as well as highlights current issues in this area. Conclusions. Cooperation of the Ministry of Internal Affairs of Ukraine with the police departments of the European Union and NATO is one of the priority areas. Further research in this area should be associated with the detailed development of certain problems of administrative and legal regulation in the analyzed area. In particular, this concerns the issue of legal regulation of the Ministry of Internal Affairs of Ukraine using the experience of the European Union and NATO. The paper draws conclusions on the possibility of using areas to improve the interaction of the Ministry of Internal Affairs of Ukraine with the police departments of the European Union and NATO in the field of management training